Augustan Rome and the Body of Christ: A Comparison of the Social Vision of the Res Gestae and Paul's Letter to the Romans - Harrison, James R. (Harvard theological review, 2013)
A surprising omission in New Testament studies of the imperial world is a comparison of Augustus's conception of rule in the Res Gestae (RG) with Paul's eschatological gospel of grace in his letter to the Romans. Even though each document has been foundational in the history of Western civilization, a comparison of their vastly different social outcomes has not been undertaken. Neil Elliott has made an outstanding contribution in laying the foundations for such a study, offering a scintillating analysis of Paul's letter to the Romans in terms of iustitia (justice), clementia (mercy), pietas (piety), and virtus (valor), the four virtues of Augustus inscribed on the Golden Shield erected in the Julian senate house (RG 34.2). However, a full-scale investigation of the Augustan conception of rule in the RG would open up new perspectives on Paul's engagement with the imperial world in Romans, given that Augustus became the iconic exemplum of virtue for his Julio-Claudian successors. Nonetheless, the difference in genre and aims of each document makes such a comparison daunting for New Testament scholars, as does the controversy that each document continues to generate in its own discipline. Further, we are unsure about the extent of the exposure that Paul might have had to the RG, directly or indirectly. Possibly Paul saw a Greek version of the RG text at Pisidian Antioch, along with the Latin text that still survives there, during his first missionary journey (Acts 13:14–50), even though there are no archaeological remains of the Greek text at Antioch today. Presumably Paul would have been aware that the original Latin copy of the RG was inscribed in bronze at Augustus's mausoleum at Rome. This article will argue that Paul, in planning to move his missionary outreach from the Greek East to the Latin West (Rom 15:19a–24), thought strategically about how he was going to communicate the reign of the crucified, risen, and ascended Son of God to inhabitants of the capital who had lived through the “Golden Age” of grace under Augustus and who were experiencing its renewal under Nero. What social and theological vision did Paul want to communicate to the city of Rome in which Augustus was the yardstick of virtue to which future leaders of Rome should aspire?